Impacts of homoepitaxial AlN thickness on the qualities of AlGaN QWs fabricated on the face-to-face annealed sputter-deposited AlN templates - Ryota Akaike; Kenjiro Uesugi; Kohei Shima; Shigefusa F. Chichibu; Akira Uedono; Takao Nakamura; Hideto Miyake (Applied Physics Express)
AlGaN quantum wells (QWs) emitting at 265 nm were fabricated on face-to-face annealed sputter-deposited AlN (FFA Sp-AlN) templates with n-AlGaN and different homoepitaxial AlN thicknesses (200–2000 nm) by metalorganic vapor phase epitaxy (MOVPE). Thicker MOVPE-AlN led to higher dislocation densities. The type and concentration of vacancies in n-AlGaN, as well as the photoluminescence efficiencies and time-resolved photoluminescence lifetimes of the QWs were nearly unchanged regardless of the MOVPE-AlN thickness, suggesting nearly identical internal quantum efficiencies. The results prove high-quality AlGaN QW growth with only 200 nm thick MOVPE-AlN, resulting in reduced total thickness of AlN by using FFA Sp-AlN.